Seroprevalence of ruminant pestivirus in breeding sheep in the central sierra of Peru - Llancares A., Nathalie (2012)
The aim of the present study was to determine the prevalence of Bovine Viral Diarrhea virus (BVDV) and Border Disease virus (BDV) in breeding sheep from a large cooperative farm in the central highlands of Peru. Blood samples from apparently healthy sheep of 4 years old, both sexes (female = 165; male = 165) were collected for antibodies detection against BVDV and BDV using the virus neutralisation test. The 2.1 ± 1.5% (7/330) and 28.5 ± 4.9% (94/330) of breeding sheep had antibodies against BVDV and BDV respectively, with antibodies titers of 1:2 and 1:16. There was significant association between sex and presence of antibodies against BDV (females: 53.3 ± 7.6%; males: 3.6 ± 2.9%) (p<0.05).